Noise characteristics of Ni/GaN Schottky barrier IMPATT diode based on polar- and nonpolar-oriented wurtzite GaN for terahertz application. (March 2020) - Zhang, Xiao-Yu; Yang, Lin-An; Ma, Yao; Liu, Yu-Chen; Yang, Wen-Lu; Ma, Xiao-Hua; Hao, Yue
Abstract: This paper reports a study investigating the noise performance of Ni/GaN Schottky barrier impact-ionization-avalanche-transit-time (IMPATT) diodes based on the polar- and nonpolar-oriented wurtzite GaN by a numerical simulation. Results show that the nonpolar IMPATT diode exhibits a significant wider and higher frequency-band corresponding to the low noise measure (NM). The upper limit of the low-noise frequency-band of the IMPATT diode shifts from 159.2 GHz to 184.3 GHz, from 183.4 GHz to 245.7 GHz and from 212.2 GHz to 285.6 GHz when J 0 = 1 kA/cm 2, 10 kA/cm 2 and 100 kA/cm 2, respectively, comparing the polar with the nonpolar IMPATT diodes. Our analysis proves that the mechanism comes from excellent properties of the Negative Differential Mobility (NDM) characteristic in the nonpolar orientation wurtzite GaN. In particular, the nonpolar diode still demonstrates better unity between the noise and RF power performances and can significantly improve the stability of IMPATT diodes at terahertz frequency. Highlights: Models of the carrier mobility characteristic and the impact ionization coefficient in wurtzite GaN were applied. The upper limit of the low-noise frequency-band of the nonpolar IMPATT diode increases obviously than the polar one. The mechanism comes from the excellent Negative Differential Mobility characteristic in the nonpolar wurtzite GaN. The nonpolar IMPATT diode demonstrates better unity between the noise and RF power performances.